Natural coloration of wood material by red beetroot (Beta vulgaris) and determination color stability under UV exposure - Yeniocak,Mehmet (Universidad del Bío-Bío, 2015)
This study is aimed to develop an eco-friendly wood stained extracted from beetroot (Beta vulgaris) and determine the color stability of this stain to UV light irradiation. Natural dyestuff were extracted from beetroot by ultrasonic-assisted method and prepared from aqueous solution with ferrous sulphate, aluminum sulphate, copper sulphate and vinegar mordant mixes. Scots pine (Pinus sylvestris), oriental beech (Fagus orientalis), oak (Quercus petraea) and walnut (Juglans regia) wood specimens were used for the study. After treatment with stain, wood specimens were exposed to UV irradiation for periods of 50, 100 and 150 hours. Results showed that the color change values for all wood specimens colored with beetroot extract had better performance compared to synthetic dye. Beetroot extracts may be used as an upper surface dyestuff for indoor application and toys. Therefore, alternative to synthetic dyes more economical and eco-friendly, wood paints may be developed.